Differences in Some Motor Abilities of Girls Engaged and those that are not Engaged with Aesthetic Activities - Ivana Cosic Mulahasanovic; Amra Nožinović Mujanović; Edin Mujanović; Almir Atikovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
Study aim was to analyze the difference in motor abilities for assessing coordination in rhythm and frequency of movement, between those girls whose only physical activity is clasess of physical and health education at school and those which are for two or more years involved with aesthetic activities, ie. sports such as dances, rhythmic gymnastics and majorette dance. The participants in this research were 62 girls, from 8-10 years of age, out of which 31 girls engaged with aesthetic activities and 31 of them are girls who are not involved in any sports except regular classes of physical and health education. Using Independent Samples T-Test we see that the examinees differ on a statistically significant level in most variables for assessment coordination in rhythm and frequency of movement, and that all values in used variables for girls engaged with aesthetic activities are higher than the values in girls who are not engaged in aesthetic activities, for which it can be said that the results are in favor of girls engaged in aesthetic activities.